Neglected Surgical Site Infection due to Multi-Drug Resistant Acinetobacter baumannii and Klebsiella pneumoniae - Kevin Kevin; Lenni Evalena Sihotang; Restuti Hidayani Saragih (Rumah Sakit Penyakit Infeksi Prof Dr. Sulianti Saroso, 2025)
Background: Surgical Site Infections (SSI) are post-operative infections often caused by ESKAPE pathogens. These multidrug-resistant bacteria, identified by the WHO as a critical threat, typically result in severe wound infections and extended hospital stays. Case Presentation: A case of a 26-year-old male with an incisional surgical site infection (SSI) in the suprapubic area that worsened due to various management errors, prolonging the patient's wound healing, but was successfully managed with a holistic approach by a multidisciplinary team, including nutritional improvement, wound care, and rational antibiotic use, which were crucial for the success of the therapy. Conclucion: Effective management of ESKAPE-related SSIs requires targeted diagnostics, a holistic multidisciplinary strategy, and robust antimicrobial stewardship programs to improve outcomes.